The need and possibility for a secret intelligence gathering reform (Academic Journal of Internal Affairs, 2015)
In order to facilitate the ongoing criminal procedure reforms, the author presents a new concept for secret intelligence in Hungary.
Keywords: secret intelligence; refirms; Hungary